Analisis Perencanaan Bangunan Bendung untuk Kebutuhan Air Irigasi di Das Way Pemerihan Kecamatan Bengkunat Kabupaten Pesisir Barat - Ridwan, Ridwan; Amin, Muhammad; Asmara, Sandi; Ramadhani, Julia (abe.fp.unila.ac.id, 2022)
The need for irrigation water in Weir building planning is needed to increase the production of irrigation areas by taking into account the availability of water and water needs. Therefore the purpose of this study is to determine the amount of water that must be accommodated by the weir so that the optimal planting area with the right planting pattern in the District of Bengkunat, West Coast Regency. The area of irrigation area of 152 ha and the area of Weir capacity of 17.7 ha and the height of the Weir from the simulation results is 11.29 m so as to obtain the volume of Weir capacity of 991,200 m3 with the source of irrigation water comes from the watershed way Pemerihan. Analysis of irrigation water needs includes regional water balance, land preparation, consumptive use, perlocation, and mainstay discharge. The use of geographic information systems and SWAT (Soil and Water Assessment Tool) will help the analysis process of irrigation water needs. The maximum value of irrigation water needs for the first and second planting period is 3.75 m3/sec which occurs in December the second two weeks and May the first week. Mainstay discharge sufficient water needs in the first and second growing season. The optimal crop area is for corn plants with an area of 70 ha. The recommended planting pattern in Bengkunat District is rice-Padi-palawija.Keywords: Irrigation Water Needs, Mainstay Discharge, SWAT, Weir.